2004
DOI: 10.1007/s00467-004-1706-7
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent focal glomerulosclerosis in pediatric renal allografts: the Miami experience

Abstract: Recurrence of focal glomerulosclerosis (FSGS) following renal transplantation is a common cause of allograft loss and clinical morbidity. Recent attempts to control proteinuria and morbidity with plasmapheresis (PP) have met with limited success. Our experience with the use of mycophenolate mofetil (MMF) and angiotensin blockade (AB) in the management of refractory FSGS pre transplant suggested its potential benefit in post-transplant recurrence. This report presents our 25-year experience in pediatric renal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 23 publications
3
66
1
Order By: Relevance
“…Plasmapheresis Plasma-based treatments, primarily plasmapheresis, have been used as a first-line treatment for FSGS and for recurrent FSGS after transplantation for nearly 20 years [5,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The results of select studies performed since the year 2000 with larger numbers of patients are summarized in Table 2.…”
Section: Treatmentmentioning
confidence: 99%
“…Plasmapheresis Plasma-based treatments, primarily plasmapheresis, have been used as a first-line treatment for FSGS and for recurrent FSGS after transplantation for nearly 20 years [5,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The results of select studies performed since the year 2000 with larger numbers of patients are summarized in Table 2.…”
Section: Treatmentmentioning
confidence: 99%
“…recurrence, rejection, hypertension). The precise recommendations for the treatment of these causes of proteinuria are beyond the scope of this review article and are covered comprehensively elsewhere [28,56,57,59].…”
Section: Causal Treatmentmentioning
confidence: 99%
“…Some studies showed an impaired graft survival in FSGS patients [29,55], whereas others did not find any differences in graft survival between recurrent FSGS patients and non-FSGS children [56,57]. Unpublished data from a retrospective study conducted in our transplantation center show that children (without recurrent FSGS) with pathological proteinuria at 1-year post-transplant have significantly worse long-term graft survival than those with normal proteinuria at 1-year post transplant.…”
Section: Consequences To Renal Allograftmentioning
confidence: 99%
“…FSGS accounts for 9 % of pediatric patients with ESRD receiving a transplant in North America, and children with ESRD secondary to FSGS have a high rate (30-86 %) of recurrence of proteinuria after renal transplant [39][40][41][42]. Graft failure is more common among patients with recurrence, and the duration of graft survival is lower among patients with FSGS than among those with other causes of glomerular disease [43,44].…”
Section: Post-transplant Recurrence Of Fsgsmentioning
confidence: 99%